Strengthening the School Community Connection. Schools in an Aging Society (Distributed by ERIC Clearinghouse, 1992)
Schools can help young people be aware of the social, political, and economic consequences of an aging society. This report is part of a six-part series, "Schools in an Aging Society," designed to promote education for, with, and about older adults. The Advanced Generations' Education through the Schools (AGES) is a planning model in Connecticut that promotes awareness of older adults through staff development, intergenerational exchange projects, curricular activities, curriculums on aging, and other activities. Eight steps are involved in designing an AGES program at either a systemwide or schoolwide level: (1) project initiator discusses the model with administrators; (2) staff and community members meet with project initiator for introduction and creation of planning committee; (3) existing programs are assessed; (4) planning committee reviews readiness and sets priorities; (5) plans are implemented; (6) the program is evaluated; (7) the projects are publicized; and (8) an annual review is conducted. Interest in the AGES program can be generated among students, teachers, parents, and older adults by addressing groups and meetings or working through governmental agencies. Appendices include a brief description of a systemwide ACES program, a brief description of how school-based AGES program was developed, professional development suggestions, and a list of national and state resources. (JPT)